Distinct Hox protein sequences determine specificity in different tissues - Chauvet, Sophie (The National Academy of Sciences, 2000)
Hox genes encode evolutionarily conserved transcription factors that control the morphological diversification along the anteroposterior (A/P) body axis. Expressed in precise locations in the ectoderm, mesoderm, and endoderm, Hox proteins have distinct regulatory activities in different tissues. How Hox proteins achieve tissue-specific functions and why cells lying at equivalent A/P positions but in different germ layers have distinctive responses to the same Hox protein remains to be determined. Here, we examine this question by identifying parts of Hox proteins necessary for Hox function in different tissues. Available genetic markers allow the regulatory effects of two Hox proteins, Abdominal-A (AbdA) and Ultrabithorax (Ubx), to be distinguished in the Drosophila embryonic epidermis and visceral mesoderm (VM). Chimeric Ubx/AbdA proteins were tested in both tissues and used to identify protein sequences that endow AbdA with a different target gene specificity from Ubx. We found that distinct protein sequences define AbdA, as opposed to Ubx, function in the epidermis vs. the VM. These sequences lie mostly outside the homeodomain (HD), emphasizing the importance of non-HD residues for specific Hox activities. Hox tissue specificity is therefore achieved by sensing distinct Hox protein structures in different tissues.